Effects of the Antitussive Drug Cloperastine on Ventricular Repolarization in Halothane-Anesthetized Guinea Pigs - Akira Takahara; Kaori Fujiwara; Atsushi Ohtsuki; Takayuki Oka; Iyuki Namekata; Hikaru Tanaka (Elsevier, 2012)
Cloperastine is an antitussive drug, which can be received as an over-the-counter cold medicine. The chemical structure of cloperastine is quite similar to that of the antihistamine drug diphenhydramine, which is reported to inhibit hERG K+ channels and clinically induce long QT syndrome after overdose. To analyze its proarrhythmic potential, we compared effects of cloperastine and diphenhydramine on the hERG K+ channels expressed in HEK293 cells. We further assessed their effects on the halothane-anesthetized guinea-pig heart under the monitoring of monophasic action potential (MAP) of the ventricle. Cloperastine inhibited the hERG K+ currents in a concentration-dependent manner with an IC50 value of 0.027 μM, whose potency was 100 times greater than that of diphenhydramine (IC50; 2.7 μM). In the anesthetized guinea pigs, cloperastine at a therapeutic dose of 1 mg/kg prolonged the QT interval and MAP duration without affecting PR interval or QRS width. Diphenhydramine at a therapeutic dose of 10 mg/kg prolonged the QT interval and MAP duration together with increase in PR interval and QRS width. The present results suggest that cloperastine may be categorized as a QT-prolonging drug that possibly induces arrhythmia at overdoses like diphenhydramine does. Keywords:: cloperastine, antitussive drug, hERG K+ channel, QT interval, monophasic action potential